(untitled) (Palíndromo, 2015)
This study comes from a micro inter- vention in a shelter for minor-age children in Rio Grande / RS. The proposal provides a link between teaching, research and ex- tension through a drawing workshop with children and youth, totaling ten partici- pants. The general objective was to engen- der an aesthetic trans praxis and, through this, to promote the graphic development and the exercise of a sensitive knowledge in the pedagogical practice and research. The subject in question expounded on how to boost a praxis that enables the aesthetic trans movement and examined which sen- sitive knowledge emerge in the process. Authors like João Franscisco Duarte Jr. and Cleusa Peralta-Castell contributed to this research on graphics and Aesthetic Educa- tion. We verified an increase on the graph- ical perception, as well as an improvement concerning pedagogical practice and the aesthetic experience produced through art education. We understand that this teaching is able to transdisciplinary integrate ways of being, living and learning in contemporary times.